Windows of opportunities and technological innovation in the Brazilian pharmaceutical industry - Paulo Bastos Tigre; Caio Victor Machado França do Nascimento; Laís Silveira Costa
Abstract: The Brazilian pharmaceutical industry is heavily dependent on external sources of inputs, capital, and technology. However, the emergence of technological opportunities and the development of biotechnology and the decline of the patent boom and resulting advances by generic drugs have opened windows of opportunities for the local industry. The article examines the Brazilian industry's innovative behavior vis-à-vis these opportunities, showing that although the industry as a whole invests little in innovation, a few large Brazilian companies have expanded their market share and stepped up their investments in research and development, supported by public policies for innovation.